Analisis Tingkat Keparahan Penyakit pada Daun Tanaman Pangan dengan Menggunakan Software ImageJ dan Plantix - Imam Rosadi; Cici Lis Qurrotun Ayuni; Indah Nurcahyani; Muhammadiyah Muhammadiyah; Irene Putri Priscilla Butar-Butar; Linda Oktavianingsih (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Plant disease is the physiological process that causes them to become abnormal. Plant diseases attack vegetative organs in the form of roots, stems, and leaves or generative organs of these plants. Plants become sick due to fungi, bacteria, or viruses that cause many symptoms of disease in plants, such as yellow spots, infection, and nitrogen deficiency (N). The purpose of this case study was to determine the severity of disease on gourds leaves (Lagenaria siceraria), bitter melon leaves (Momordica charantia), cassava leaves (Manihot esculenta), purple eggplant leaves (Solanum melongena), and terung pipit leaves (Solanum torvum) by using the Plantix software and ImageJ software methode. Based on the results of this case study, it was found that the severity of disease using ImageJ software on gourds leaves (4.56%), bitter melon leaves (1.93%), cassava leaves (8.49%), purple eggplant leaves (49.45%) and terung pipit leaves (14.88%) which are generally food crops are caused by viruses and fungiand based on the results of the Plantix software data, the causes of gourds leaves, bitter melon leaves, cassava leaves, purple eggplant leaves and terung pipit leaves respectively are caused by downy mildew, fungus, whitefly, leaf spot algae and leafhoppers.